MANAJEMEN KESEHATAN PENCEGAHAN CARIES PADA ANAK DENGAN MENJAGA KEBERSIHAN GIGI DAN MULUT - Panzilion Panzilion; Ferasinta Ferasinta; Andry Sartika; Leni Rozani (Jurnal Pengabdian, 2023)
Dental caries is a disease of the hard tissue of the teeth caused by bacterial activity. Dental caries can occur in every child which can arise on the surface of the teeth and can extend to deeper parts of the teeth. The purpose of this activity is to know the health management of caries prevention in children through dental and oral hygiene. Activities carried out for all parents and children at the Betungan Health Center. The activity was carried out by providing education in the form of counseling using the lecture method with the help of projector media and leaflets. The time required to deliver the material is 30 minutes. The participants in the community service activities at the Betungan Health Center were very enthusiastic so that the activities ran smoothly.